2013
DOI: 10.1159/000354722
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Analogue CXC195 Protects against Cerebral Ischemia/Reperfusion Injury in the Rat by an Antioxidant Action via Inhibition of NADPH Oxidase and iNOS Expression

Abstract: Aims: This study was conducted to investigate the protective effects of CXC195, a tetramethylpyrazine analogue, in acute focal cerebral ischemia/reperfusion (I/R) injury in rats and to elucidate the potential mechanism. Methods: Middle cerebral artery occlusion for 2 h followed by reperfusion for 24 h was conducted in male Wistar rats and different doses of tetramethylpyrazine and CXC195 were intraperitoneally injected at 30 min after reperfusion. Results: Our results demonstrated that CXC195 at the dosage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 75 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…Accordingly, we have found that elevation of miR‐155 by ischemia and L‐NIO is paralleled by an elevation of the percentage of CD40 + /CD68 + M1 microglia macrophages, which is coincident with an increase of iNOS mRNA expression in immune cells isolated by Percoll gradient from the ischemic cortex. This latter finding is consistent with previous observations demonstrating elevation of iNOS protein levels after 1‐hr MCAo followed by 24 hr of reperfusion (Liu et al, ; Niu et al, ; Tsai et al, ) and suggests that eNOS inhibition promotes inflammatory responses in local microglia and infiltrating leukocytes that contribute to ischemic brain injury. Accordingly, previous findings have shown that iNOS both in neutrophils and endothelium mediates ischemic tissue damage (Garcia‐Bonilla et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, we have found that elevation of miR‐155 by ischemia and L‐NIO is paralleled by an elevation of the percentage of CD40 + /CD68 + M1 microglia macrophages, which is coincident with an increase of iNOS mRNA expression in immune cells isolated by Percoll gradient from the ischemic cortex. This latter finding is consistent with previous observations demonstrating elevation of iNOS protein levels after 1‐hr MCAo followed by 24 hr of reperfusion (Liu et al, ; Niu et al, ; Tsai et al, ) and suggests that eNOS inhibition promotes inflammatory responses in local microglia and infiltrating leukocytes that contribute to ischemic brain injury. Accordingly, previous findings have shown that iNOS both in neutrophils and endothelium mediates ischemic tissue damage (Garcia‐Bonilla et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…MDA (a ROS and an index for oxidative stress) is a critical component of NADPH oxidase and is produced through lipid peroxidation. Increased MDA levels result in the release of myocardial enzymes and their subsequent attack on structural proteins and cells [38]. Given that oxidative stress is a crucial event in I/R injury, inhibition of oxidative stress is considered a viable approach to treat I/R-induced cardiac injury.…”
Section: Discussionmentioning
confidence: 99%
“…CXC195 are known as a TMP analog and have the antioxidant activity and anti-apoptotic effect in neuron [13,14] and HUVECs [15]. Recent studies have shown that CXC195 inhibit proliferation and inflammatory response of LPS-induced human hepatocellular carcinoma HepG2 cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…CXC195 is a TMP analog showing the antioxidant activity and anti-apoptotic effect in transient focal ischemia via inhibiting NADPH Oxidase and iNOS expression [13] and regulating PI3K-AKT-GSK3b pathway [14]. In addition, CXC195 could prevent human umbilical vein endothelial cells (HUVECs) from H 2 O 2 -induced apoptosis through inhibition of the mitochondriaand caspase-dependent pathway [15].…”
Section: Introductionmentioning
confidence: 99%